2018
DOI: 10.21037/gs.2017.10.06
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of pancreatic neuroendocrine neoplasm by minimally invasive surgery—the robotic approach?

Abstract: Over the past decade, there has been increasing adoption of minimally invasive pancreatic surgery world-wide and this has naturally expanded to the management of pancreatic neuroendocrine neoplasms (PNENs). More recently, robotic pancreatic surgery (RPS) was introduced to overcome the limitations during laparoscopic pancreatic surgery (LPS). Due to the relative rarity of PNEN and the novelty of minimally invasive pancreatic surgery in particular RPS today, the evidence for robotic surgery in PNENs remains extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 72 publications
(106 reference statements)
0
22
0
Order By: Relevance
“…version rate to open surgery compared to LDP. 2,10,14,24,25 In this study, subtotal pancreatectomy was performed significantly more frequently for tumors located in the neck or body via the robotic approach. Some surgeons may propose central pancreatectomy as a parenchymasaving approach for these tumors especially when these tumors are not suggestive of invasive cancer.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…version rate to open surgery compared to LDP. 2,10,14,24,25 In this study, subtotal pancreatectomy was performed significantly more frequently for tumors located in the neck or body via the robotic approach. Some surgeons may propose central pancreatectomy as a parenchymasaving approach for these tumors especially when these tumors are not suggestive of invasive cancer.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is important to note that the costs of robotic systems will likely decrease in the near future with increasing availability and competition in the market. 18,24,39 Many investigators have demonstrated the safety and feasibility of RDP in comparison with LDP as the incidence of total postoperative complications were similar between the two. 1,2 Similarly, the results of our study showed no significant difference between RDP and LDP in terms of the frequency of total complications, major morbidity, pancreatic fistula, and readmission rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 1 2 ] In recent years, improved knowledge and standardisation of MIPS techniques in addition to rapid advancements in the development of minimally invasive surgical device technology such as the introduction of improved high-definition laparoscopes and new advanced energy devices have allowed more surgeons throughout the world to perform MIPS. [ 2 4 5 ] Hence, the indications of MIPS have expanded as surgeons gained increasing experience with MIPS,[ 1 2 6 ] from less complicated distal pancreatectomies (DP)[ 7 8 ] and enucleations[ 9 ] to more complicated procedures such as central pancreatectomies[ 10 ] and pancreatoduodenectomies (PD)[ 11 12 ] including even extended pancreatic resections requiring vascular resections. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%